Down’s Syndrome with Congenital Heart Disease: Our Surgical Experience - Islam, Md Zahidul; Jahan, Sakila Israt; Moinuddin, Shahriar; Rushel, Khondokar Shamim Shahriar Ziban; Islam, Shafiqul; Islam, Faizul; Hasan, Kazi Abul (Cardiovascular Journal, 2020)
Background: Our objective was to analyze the outcome of patients of Down’s syndrome with congenital heart diseases undergoing cardiac surgery. Methods: This was a retrospective study conducted between January 2013 and June 2019. 49 consecutive patients with Down’s syndrome with congenital heart disease admitted in pediatric cardiac surgery unit at National Institute of Cardiovascular Diseases (NICVD). Patients were followed up postoperatively for in-hospital outcome. Results: Among 49 patients the heart lesion ranked in incidence as follows- VSD 24(48.97%), AV canal defect 12(24.48%), TOF 6(12.24%), PDA 6(12.24%) and ASD 1(2.04%). Pulmonary hypertension was found in 63.25% patients. Moderate pulmonary hypertension was most common, found in 18(38.66%) patients. Severe and mild pulmonary hypertension was found in 10(32.38%) and 3(9.67%) patients respectively. All the patients had undergone surgical correction. The postoperative period was complicated in 44.89% of patients. The most frequent complication was pulmonary infection 20.40%, Wound infection 6.12% and low output syndrome 6.12% were the next. One patient had postoperative heart block, needed permanent pace maker implantation. In-hospital mortality was 12.24%. Conclusion: Patients with Down’s syndrome with congenital heart disease undergoing surgical correction had an acceptable postoperative morbidities and mortality. Cardiovasc. j. 2020; 13(1): 35-39